Impact of Hospital Safety-Net Burden on Outcomes of In-Hospital Cardiac Arrest in the United States. (9th January 2023) - Olanipekun, Titilope; Abe, Temidayo; Chris-Olaiya, Abimbola; Effoe, Valery S.; Bhardwaj, Abhishek; Harrison, Michael F.; Moreno Franco, Pablo; Guru, Pramod; Sanghavi, Devang
Abstract : IMPORTANCE: High safety-net burden hospitals (HBHs) treating large numbers of uninsured or Medicaid-insured patients have generally been linked to worse clinical outcomes. However, limited data exist on the impact of the hospitals' safety-net burden on in-hospital cardiac arrest (IHCA) outcomes in the United States. OBJECTIVES: To compare the differences in survival to discharge, routine discharge home, and healthcare resource utilization between patients at HBH with those treated at low safety-net burden hospital (LBH). DESIGN, SETTING, AND PARTICIPANTS: Retrospective cohort study across hospitals in the United States: Hospitalized patients greater than or equal to 18 years that underwent cardiopulmonary resuscitation (CPR) between 2008 and 2018 identified from the Nationwide Inpatient Database. Data analysis was conducted in January 2022. EXPOSURE: IHCA. MAIN OUTCOMES AND MEASURES: The primary outcome is survival to hospital discharge. Other outcomes are routine discharge home among survivors, length of hospital stay, and total hospitalization cost RESULTS: From 2008 to 2018, an estimated 555, 016 patients were hospitalized with IHCA, of which 19.2% occurred at LBH and 55.2% at HBH. Compared with LBH, patients at HBH were younger (62 ± 20 yr vs 67 ± 17 yr) and predominantly in the lowest median household income (< 25th percentile). In multivariate analysis, HBH was associated with lower chances of survival to hospital discharge (adjusted odds ratio [aOR], 0.88; 95% CI, 0.85–0.96) and lower odds of routine discharge (aOR, 0.6; 95% CI, 0.47–0.75), compared with LBH. In addition, IHCA patients at publicly owned hospitals and those with medium and large hospital bed size were less likely to survive to hospital discharge, while patients with median household income greater than 25th percentile had better odds of hospital survival. CONCLUSIONS AND RELEVANCE: Our study suggests that patients who experience IHCA at HBH may have lower rates and odds of in-hospital survival and are less likely to be routinely discharged home after CPR. Median household income and hospital-level characteristics appear to contribute to survival.